2002
DOI: 10.1007/bf03020523
|View full text |Cite
|
Sign up to set email alerts
|

Gender and pain upon movement are associated with the requirements for postoperative patient-controllediv analgesia: a prospective survey of 2,298 Chinese patients

Abstract: Purpose: To investigate prospectively the influence of patient characteristics upon, and the association of postoperative measurements with, the requirements for postoperative morphine and the assessment of resting pain and pain upon movement in Chinese patients.Methods: From January 1998 to December1999, patients receiving patient-controlled iv morphine subsequent to general anesthesia and surgery at our institute (Kaohsiung Veterans General Hospital), were enrolled in the study. Demographic data (such as gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
7
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(95 citation statements)
references
References 23 publications
4
80
7
4
Order By: Relevance
“…Ethnic influences in the postoperative morphine consumption that may be another reason for this difference. So, ethnic influences can be a contributing factor because our patient's requirements were comparable with the Asian studies conducted on Chinese patients by Tsui et al, [8] and Chia et al, [9]. Tsui et al, had found that the mean morphine consumption in the first 16 h and 17-41 h postoperatively were 25.7 and 17.8 mg respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Ethnic influences in the postoperative morphine consumption that may be another reason for this difference. So, ethnic influences can be a contributing factor because our patient's requirements were comparable with the Asian studies conducted on Chinese patients by Tsui et al, [8] and Chia et al, [9]. Tsui et al, had found that the mean morphine consumption in the first 16 h and 17-41 h postoperatively were 25.7 and 17.8 mg respectively.…”
Section: Discussionsupporting
confidence: 79%
“…However, in adolescent patients using PCA morphine in the postoperative period, no difference was seen between male and female patients in average daily pain ratings (Logan & Rose, 2004 Level III-2). In a study of Chinese patients, females consumed significantly less morphine than males (Chia et al, 2002 Level III-2).…”
Section: Gendermentioning
confidence: 99%
“…Abdominal hysterectomies have been associated with higher acute postsurgical pain than vaginal hysterectomies, 32 as open abdominal surgeries are among the most painful surgical procedures. 15,35 Vaginal route 42,78 or laparoscopic 14,24,52 approaches to hysterectomy should be considered when possible.…”
Section: Demographic and Clinical Baseline Predictorsmentioning
confidence: 99%